Enhancing beans (Phaseolus vulgaris) growth using zeolite-based growing media - Putri Oktariani; Andhika Septiana Suryaningsih; Dyah Tjahyandari Suryaningtyas (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Electrical conductivity (EC) spikes due to fertilization are harmful to plant. This shows the need for appropriate composition of growing media, such as Zeoponic, consisting of zeolite, cocopeat, and compost, to support plant development. Therefore, this study aimed to determine the effect of zeolite-based growing media and the addition of fertilizer on growth of bean (Phaseolus vulgaris) cultivated in polybags. The experiment was conducted on beans in three different media with a completely randomized design (CRD) in factorial arrangement, with three levels type treatment (zeoponic, media A, and B), and three levels of fertilizer dosage (0 g kg-1, 1 g kg-1, 1.5 g kg-1). The parameters observed were plant height, number of leaves, beans weight, length, and disease intensity. The results showed that growth and production of beans in zeoponic tended to be higher than in A and B. However, the addition of fertilizer at 1.5 g kg-1 did not significantly affect growth and production of beans. The presence of zeolite caused EC of the growing media to remain low, and nutrients were released slowly to ensure continuous availability to plant. Additionally, the use of zeoponic for cultivating beans in polybags has been shown to reduce the incidence of disease.